العوامل المؤثرة في تقديرات طلبة الجامعات للأداء التدريسي لأعضاء هيئة التدريس - الكيلاني، عبدالله زيد (جامعة الملك سعود - كلية التربية, 2013)
هدفت هذه الدراسة إلى تعرّف العوامل المؤثرة في تقديرات طلبة الجامعات للأداء التدريسي لأعضاء هيئة التدريس فيها، بالإضافة إلى استقصاء مصادر الخطأ وعوامل التحيّز في تقديرات الطلبة، وكم يتحقق لها من دلالات الصدق والثبات، وكيف يمكن تعزيز سبل الاستفادة من نتائجها في تحسين التدريس الجامعي. اعتمدت منهجية الدراسة على مصدرين للبيانات: الأول نتائج مراجعة دراسات سابقة حول محاور ذات صلة بأسئلة الدراسة، والثاني استجابات 642 من أعضاء هيئة التدريس في ثماني جامعات أردنية لاستطلاع للرأي تضمَّن 13 فقرة، تناولت جوانب محددة في تقويم الطلبة لمدرّسيهم. من العوامل التي كشفت عنها مراجعة الدراسات السابقة ما له علاقة بمتغيرات موقفية في طبيعة المساق، وعضو هيئة التدريس، والطالب، وأداة التقويم، ومن العوامل الأخرى التي أشارت إليها نتائج دراسات أخرى: عدم تحقق أحادية البعد في تقديرات الطلبة، والاختلاف بين الطلبة ومدرسيهم حول معايير فاعلية التدريس، وعدم توفر دلالات كافية عن صدق تقديرات الطلبة وثباتها. وكشفت نتائج استطلاع آراء أعضاء هيئة التدريس في الجامعات الأردنية عن ثلاثة عوامل رئيسية مشبعة بفقرات تعبّر عن متغيرات تؤثر في تقديرات الطلبة، والحاجة إلى أن يكون تقويم فاعلية التدريس أكثر شمولية، وعن مدى توافر الدقة والموضوعية في تقديرات الطلبة. كما كشفت النتائج عن أساليب يمكن أن تعزز طرق الاستفادة من نتائج تقويم الطلبة. The purpose of this study was to identify factors affecting university student ratings of faculty teaching performance. This purpose also included investigating sources of error and bias in students’ ratings, ascertaining evidence of their validity and reliability, and how to enhance their usefulness in improving instruction. The methodology utilized two sources of information. The first consisted of findings from a number of reviewed studies compiled around the major research questions. The second source was the opinions of 642 faculty members in eight Jordanian public universities, who responded to a questionnaire consisting of 13 items related to certain aspects of student evaluation of faculty. The findings from reviewed studies identified a number of contextual variables related to the course, the instructor, the student, and the evaluation tool. Other factors identified in other studies included: dimensionality of student ratings, differences between instructors and students about criteria of teaching efficiency, and the lack of sufficient evidence on the validity and reliability of students’ ratings. Still other findings yielded factors related to the effect of class size, course level, and student absenteeism. The results of factor analysis of faculty opinion responses revealed three significant factors that had factor loadings in items related to a number of variables affecting student ratings, the need to reconsider more comprehensive ways of evaluating teaching performance, and the extent to which student ratings could be considered accurate and objective. Based on findings identified in this study, a number of ways were recognized to enhance the usefulness of student ratings in improving instructional performance.
783675
Keywords: تقييم الأداء -- الأردن -- الجامعات والكليات -- طلاب الجامعات -- هيئة التدريس -- مهارات التدريس -- التقييم التربوي -- المعايير التربوي